2021
DOI: 10.4251/wjgo.v13.i9.1164
|View full text |Cite
|
Sign up to set email alerts
|

Scoparone inhibits pancreatic cancer through PI3K/Akt signaling pathway

Abstract: BACKGROUND Pancreatic cancer is a highly malignant tumor of the gastrointestinal system whose emerging resistance to chemotherapy has necessitated the development of novel antitumor treatments. Scoparone, a traditional Chinese medicine monomer with a wide range of pharmacological properties, has attracted considerable attention for its antitumor activity. AIM To explore the potential antitumor effect of scoparone on pancreatic cancer and the possible molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Increasing studies have demonstrated the antitumor effects of TCM on the proliferation, metastasis, and tumorigeneis in cancer development [ 8 ]. In pancreatic cancer, it has been reported that scoparone inhibits tumor progression via PI3K/Akt signaling pathway [ 9 ]. Besides, a proteoglycan extracted from Ganoderma lucidum can induce cancer cell apoptosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have demonstrated the antitumor effects of TCM on the proliferation, metastasis, and tumorigeneis in cancer development [ 8 ]. In pancreatic cancer, it has been reported that scoparone inhibits tumor progression via PI3K/Akt signaling pathway [ 9 ]. Besides, a proteoglycan extracted from Ganoderma lucidum can induce cancer cell apoptosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preset all available gene sets, p -value cutoff (FDR, adjusted in the hypergeometric test) < 0.05 and show the top 30 pathways. Finally, the candidate drugs from the STITCH database are screened out from the enrichment results.STITCH ( Li et al, 2021 ) ( http://stitch.embl.de/ ) is a powerful search tool for predicting drug-target relationships. In this analysis, we used 42 genes shared by COVID-19 and COPD to predict drug candidates for COVID-19 and COPD comorbidities.…”
Section: Methodsmentioning
confidence: 99%
“…Scopolone is a traditional Chinese medicine phenylpropane monomer. It has a wide range of pharmacological activities, and its antitumor activity has been confirmed in leukemia, laryngeal cancer, and prostate cancer [ 24 , 25 ]. However, we still need to continue to study and use more convincing evidence to explain the potential molecular mechanism of its antitumor activity.…”
Section: Discussionmentioning
confidence: 99%